Protein for Community-Dwelling Older People: Aspects That Influence the Perception of Commercially Available Protein Drinks - Lampmann, Lyn; Hannink, Anne; Kiesswetter, Eva; Emberger-Klein, Agnes; Volkert, Dorothee; Menrad, Klaus (Frontiers in Nutrition, 2020)
In an aging population support for independent living is increasingly critical for older generations. Currently, sarcopenia is a major cause of frailty which increases the risk of decreased mobility, falls, morbidity and mortality and leads to dependency on third parties. Sarcopenia is preventable by consumption of adequate protein. However, many older people do not meet the recommended daily allowance of protein, thereby supporting dependency rather than independent living. Current literature indicates that a protein drink could be an appropriate product for older peoples´ protein consumption. We were interested in autonomous persons, whose nutritional decisions were still self-determined and thus could preventively influence their personal health. This study evaluated three commercially available protein drinks in three focus groups (n=25) to gain insight into which aspects influence the perception of commercial protein drinks on community-dwelling older people (age: 76.8 ± 4.9).Findings from the focus groups revealed only aspects which influenced the perception of commercial protein drinks negatively. Most importantly the drinks did not comply with relevant aspects when buying (healthy) foods, which where: naturalness, freshness, locally grown ingredients and trust. Furthermore, the target group did not see a need for additional protein consumption.Thus, we identify important aspects to be considered for the development of a target group specific protein drink as well as more suitable communication to prevent distrust in order to support independent living for community-dwelling older people.